(3QSGdI aj GdJUhas - (3YOj Hf eSGaQ Hf ESeGYjd GdgcGQj, TQa GdOjf CHh GdaVGFd,J (B557 (3g` s
(3ChdgG (B:s
(3aUd ai EYJbGO Cgd GdSfI hGdLeGYI s
(3BNQgG (B:s
(3hbGd YHO Gddg Hf eSYhO QVi Gddg Yfg EJHYhG hdG JHJOYhG abO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B275s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdeLGejYs